Sugar Shock: Probing Streptococcus pyogenes Metabolism Through Bioluminescence Imaging - Davis, Richard W.; Muse, Charlotte G.; Eggleston, Heather; Hill, Micaila; Panizzi, Peter (Frontiers in Microbiology, 2022)
Streptococcus pyogenes (S. pyogenes) can thrive in its host during an infection, and, as a result, it must be able to respond to external stimuli and available carbon sources. The pre-clinical use of engineered pathogens capable of constitutive light production may provide real-time information on microbial-specific metabolic processes. Here we mapped the central metabolism of a luxABCDE-modified S. pyogenes Xen20 (Strep. Xen20) to its de novo synthesis of luciferase substrates as assessed by the rate of light production in response to different environmental triggers. Previous characterization predicted that the lux operon was under the myo-inositol iolE promotor. Here we show that supplementation with myo-inositol generated increased Xen20 luminescence. Surprisingly, when supplemented with infection-relevant carbon sources, such as glucose or glycine, light production was diminished. This was presumably due to the scavenging of pyruvate by L-lactate dehydrogenase (LDH). Inhibition of LDH by its inhibitor, oxamate, partially restored luminescent signal in the presence of glucose, presumably by allowing the resulting pyruvate to proceed to acetyl-coenzyme A (CoA). This phenomenon appeared specific to the lactic acid bacterial metabolism as glucose or glycine did not reduce signal in an analogous luxABCDE-modified Gram-positive pathogen, Staph. Xen29. The Strep. Xen20 cells produced light in a concentration-dependent manner, inversely related to the amount of glucose present. Taken together, our measures of microbial response could provide new information regarding the responsiveness of S. pyogenes metabolism to acute changes in its local environments and cellular health.